Cultura e patrimônio - Galves, Beatriz Lourenço Peixoto (2008)
This thesis presents a reflection upon the notions of culture and historical-cultural heritage as presupposition for understanding the activities of the Conselho de Defesa do Patrimônio Histórico, Arqueológico, Artístico e Turistico [Council for the Defence of the Historical, Archaeological, Artistic and Touristit Heritage] of the State of São Paulo Condephaat. The Council was crated in São Paulo by federal determination during the first years of the military dictatorship. The finality of the council is to protect, appraise and divulgate the cultural heritage of São Paulo by means of the juridical institution known as tombamento [listing/classifying]; its attribution as confirmed by the State Constitution. This heritage forms a group of representative historical and cultural heritage elements within the 16th and 20th centuries. It encompasses objects, edifications, monuments, districts, historical nucleus and natural areas. The understanding of what historical-cultural heritage is was initially identified to the monuments and to the architectonic edifications. It has enlarged and went beyond a symbolic notion to other competencies permeated by consumption and spectacle. The word culture is like a chameleon and may be understood and interpreted in multiple and complementary meanings. It has obtained its status as a concept within the academic circles during the XX century. During the years 1930s, when the Serviço de Proteção ao Patrimômio Histórico [Service for the Protection of the Cultural Heritage] Sphan - was created in Brazil, the term culture reached a theoretical position of glorification and became one of the most important ones in anthropological literature: cultural traces, cultural complexes, cultural types, cultural centres, cultural migrations, convergences, cultural diffusion. Every discussion on culture contains the omnipresent idea o the pre-cultural biological unity of the human condition. Human groups keep together by means of a net of communication and exchanges. Immerse into a pluralistic and heterogeneous social context, the individual receives this duality from reality itself; it is an intuitive and pre-theoretical experience in essence. The nature-culture duality is a key-problem of the conceptual effort in this thesis. Keeping it as fragmental opposition means to reinforce the premises of the Cartesian paradigm; it demands a complex and transdisciplinar interpretative effort to overcome it in the direction of dialogical approach. From this point of view, this thesis discovers a paradoxal position assumed by the Condephaat in its obscure politics of heritage preservation, which oscillates among protectionisms, disobediences and negligent behaviour and the effort of individuals trapped in external interests which immobilizes them in many opportunities. The attempts to dilapidate the heritage in São Paulo reveal a predatory violence transfigured as progress. The activities of the council were analysed by mean of reading the processes for listing heritage and by mean of interviews. Many presidents of the Council between 1979 and 2007 were interviewed. There is room for the voice of people who live at the listed district of Pacaembu who are either leaders of the local residents´ associations, Associação de Moradores e Amigos de Perdizes, Pacaembu e Higienópolis [Residents and Friends Association of Perdizes, Pacaembu and Higienópolis], Amapph, and the Associação Viva Pacaembu por São Paulo [Living Pacaembu for São Paulo Association], or had active participation in opening the process for listing the district